ANALISIS KESULITAN MAHASISWA DALAM PERKULIAHAN DAN PRAKTIKUM KIMIA DASAR DI JURUSAN PENDIDIKAN BIOLOGI FKIP UNISBA - Dian Puspita Anggraini (Universitas Islam Balitar, 2016)
The objective of this study is to see reasons of learning obstacles on learning process and practicum of basic chemistry course in relation with practicum and mastery of the theory. The study used descriptive design and collected data using test and questionnaire. The study assigned 40 students of biology Class at UNISBA. The study revealed that problems on learning basic chemistry is the mastery of teaching materials. Percentage of the problems is contributed in trems of: (1) practicum process 53.29%, (2) teaching process 66.26%, and (3) practicum implementation 66.26%. On social factor, statistically contributes problems up to 66.15%.